Low-dimensional nanomaterials for the photocatalytic degradation of organic pollutants - Mishra D.; Srivastava M. (My University, 2025)
Organic pollutants with toxicity pose a serious threat to the ecological and environmental existence. It has a deleterious effect on human health and has drawn attention of the researchers to degrade the organic pollutants by using novel methods and establishing new protocols. In this chapter, a holistic overview of the type and nature of various organic pollutants is presented. The main focus of the chapter is to give a detailed description and to review various tools including hydrolysis, photolysis, oxidation, and reduction used for degradation of various contaminants recently and understanding the mechanism behind it. The role of novel functional materials including TiO2 nanoparticles, graphene nanocomposites, and magnetic nanoparticles (e.g., Fe3O4 and Fe2O3) for degradation of pollutants would be discussed briefly. The understanding of how these 1D- and 2D-based nanomaterials/nanocomposites react with pollutants and interact with the surrounding environment is critically revisited. © 2020 Elsevier Inc. All rights reserved.